Peace Has No Deterrent Effect: The Handling of Violence Against Lampung TV and Lampung Post Journalists (2022) by Press Organizations - Eddyono, Aryo Subarkah; P., Jessica Rosa N. (UI Scholars Hub, 2024)
In 2022, Lampung Post and Lampung TV journalists experienced violence while covering. The perpetrator was a member of the security unit when he wanted to ask for clarity regarding certificates in the 2017 Complete Systematic Land Registration Acceleration Program (PTSL) at the National Land Agency (BPN) of Bandar Lampung City. The BPN security guard confiscated work tools and forced journalists to delete coverage such as photos or videos, until finally forcibly expelling journalists by pushing and closing the BPN building gate. This research aims to find out why such violence can occur and how the role of press organizations resolves cases of violence against Lampung Post and Lampung TV journalists. Data were obtained from interviews, observations, and document searches. The results of the study showed that violence against Lampung Post and Lampung TV journalists occurred due to a lack of understanding of the perpetrators of violence about the duties of journalists, weak law enforcement, and a lack of support from press companies to protect and provide understanding to their journalists in conducting coverage. Press organizations in Lampung have played their role in overseeing the resolution of cases of journalist violence through the Coalition of Press Freedom Defenders (KPKP) with a series of efforts, including providing statements of attitudes and legal opinions, encouraging the authorities to investigate cases, strengthening the authorities, and holding campaigns and public discussions. Unfortunately, the role of press organizations is still not optimal because not all press organizations are involved, press companies are ignorant, and victims take peaceful initiatives. Peace desision has no deterrent effect on perpretators.In 2022, journalists from Lampung Post and Lampung TV experienced violence while reporting. The perpetrator was a member of the security unit when they went to the National Land Agency (BPN) in Bandar Lampung City to ask for clarification about certificates in the 2017 Complete Systematic Land Registration Acceleration Program (PTSL). The BPN security personnel confiscated work tools and forced journalists to delete coverage such as photos or videos, until finally forcibly expelling journalists by pushing and closing the gate of the BPN building. This research aims to find out why such violence can occur and how the role of press organizations resolves cases of violence against Lampung Post and Lampung TV journalists. Data was collected through interviews, observations, and document review. The results of the study showed that violence against Lampung Post and Lampung TV journalists occurred due to perpetrators' lack of understanding of journalists' duties, weak law enforcement, and lack of support from press organizations to protect and provide understanding to their journalists in reporting. Press organizations in Lampung have played their role in monitoring the resolution of cases of violence against journalists through the Coalition of Press Freedom Defenders (KPKP) with a series of efforts, including providing statements and legal opinions, encouraging the authorities to investigate cases, strengthening the authorities, and holding campaigns and public discussions. Unfortunately, the role of press organizations is still not optimal because not all press organizations are involved, press companies are ignorant, and victims take peaceful initiatives. Peace initiatives do not have a deterrent effect on perpetrators.